2011
DOI: 10.1002/clen.201000477
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Copper, Nickel, and Zinc Ions from Electroplating Rinse Water

Abstract: Research Article Removal of Copper, Nickel, and Zinc Ions from Electroplating Rinse WaterRemoval of copper, nickel, and zinc ions from synthetic electroplating rinse water was investigated using cationic exchange resin (Ceralite IR 120). Batch ion exchange studies were carried out to optimize the various experimental parameters (such as contact time, pH, and dosage). Influence of co-existing cations, chelating agent EDTA on the removal of metal ion of interest was also studied. Sorption isotherm data obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 46 publications
2
20
0
1
Order By: Relevance
“…In this regards, multiple researchers studied the effectiveness of various type of clay in removing heavy metals from aqueous solutions including kaolinite (Sari et al 2007;Schaller et al 2009), bentonite (Ulmanu et al 2003;Kaya and Hakan Ö ren 2005;Eren et al 2009), illite (Ozdes et al 2011), sepiolite (Guerra et al 2010), montmorillonite (Lin and Juang 2002), and other adsorbents (Al-Degs et al 2006;Engates and Shipley 2011). Many other studies have been undertaken to evaluate the adsorptive capacity of various bioadsorbents in the removal of inorganic pollutants (Ahmad et al 2010;Das 2012;Dubey and Shiwani 2012;Revathi et al 2012;Eren 2010). They found that those cheap adsorbents could be used in the removal of different metal cations [e.g., Cd(II), Pb(II), Cu(II), Zn(II) … etc.].…”
Section: Introductionmentioning
confidence: 99%
“…In this regards, multiple researchers studied the effectiveness of various type of clay in removing heavy metals from aqueous solutions including kaolinite (Sari et al 2007;Schaller et al 2009), bentonite (Ulmanu et al 2003;Kaya and Hakan Ö ren 2005;Eren et al 2009), illite (Ozdes et al 2011), sepiolite (Guerra et al 2010), montmorillonite (Lin and Juang 2002), and other adsorbents (Al-Degs et al 2006;Engates and Shipley 2011). Many other studies have been undertaken to evaluate the adsorptive capacity of various bioadsorbents in the removal of inorganic pollutants (Ahmad et al 2010;Das 2012;Dubey and Shiwani 2012;Revathi et al 2012;Eren 2010). They found that those cheap adsorbents could be used in the removal of different metal cations [e.g., Cd(II), Pb(II), Cu(II), Zn(II) … etc.].…”
Section: Introductionmentioning
confidence: 99%
“…üzerindeki doz artışının adsorpsiyon yüzdesinde belirgin değişikliğe sebep olmadığı gözlenmiştir. Çünkü adsorban dozunun artması adsorpsiyonun gerçekleştiği yüzey alanının ve adsorplama bölgelerinin artması anlamına gelmektedir [16]. Bu sebeple adsorplama yüzdesi artış göstermektedir, fakat adsorbanın gramı başına adsorplanan Zn(II) miktarı çözeltideki Zn(II) miktarının sabit olması nedeniyle azalmaktadır.…”
Section: Ph Etkisi (Effect Of Ph)unclassified
“…Because of its mobility, metal ions are very difficult to trace when they are introduced into the ecosystem, and the ultimate destination of these metal ion species is frequently unknown. [1][2][3] Among the processes for removing toxic metals from aqueous effluents are chemical precipitation, flocculation, carbon adsorption, ion exchange, reverse osmosis and electrodialysis. [3][4][5][6][7] These methods present disadvantages, including high cost or production of sludge with a high metal concentration which is difficult to dispose of.…”
Section: Introductionmentioning
confidence: 99%